SeeAround: an offline mobile live support system for the visually impaired - Sebban, Othmane; Azough, Ahmed; Lamrini, Mohamed (Institute of Advanced Engineering and Science, 2025)
The inability of blind or partially-sighted people to understand visual content and real-life situations reduces their standard of living, especially in a world mainly tailored for sighted individuals. Despite the progress made by certain devices to assist them in using touch, sound, or other senses, these solutions often fall short of bridging the comprehension gap. Our work proposes an intuitive, user-friendly mobile-based framework named